Growth at risk: Methodology and applications in an open-source platform - Matias Ossandon Busch; Manuel Sánchez-Martínez; Anahí Rodríguez-Martínez; Ricardo Monta\~nez-Enríquez; Serafín Martínez-Jaramillo (Latin American Journal of Central Banking (LAJCB), 2022)
This article describes the construction of an open-source growth-at-risk (GaR) model. The model provides a flexible analytical tool for policymakers and researchers aiming to use the GaR approach to characterize the probability density of GDP growth conditional on domestic and international macrofinancial variables. This article, together with its related online repository, aims to foster an understanding of macrofinancial risk factors both in advanced and emerging economies.
Keywords: G01; O4; O47; E44; 330; Economic growth; Financial stability; Growth-at-risk; Quantile regressions